Scenarios in education for Moran municipality, Lara state: a vision for the future (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
This paper's main objective apply the Delphi technique for the formulation of Educational Scenarios for the Morán Municipality, Lara State-Venezuela, in a timeframe of 10 years (2010-2020), based on current conditions and prospects viewing your local development. It falls in the category of a research field, with a quantitative approach, the application of Delphi in formulating scenarios, and, by mathematical techniques and procedures used. The sector was sized into four categories: Demographic Aspects, Performance Diversified and Basic Education, state support, and Higher Education Sector Performance. The results obtained leads to; in Demography, the tendency is to stay the same as it is now, because of the conflicting opinions of the experts, while in the other dimensions, the scenario tend to be positive. Although the town has great strengths and potential, is not observed in the studied time to achieve sustainable development supported by the education sector.